The Role of Banking Digitalization in Enhancing Business Capacity among Rural Communities in Indonesia - Samara, Faiz Nasrullah; Prawoto, Benny Rahardian; Maulana, Arsha; Firdaus, Arief Ridwan; Dewi, Nurma Gupita (Universitas YPPI Rembang, 2024)
The digitalization of banking has emerged as a transformative force in enhancing financial inclusion and supporting economic growth, particularly in rural communities. This study examines the role of banking digitalization in improving business capacity among rural communities in Indonesia. By leveraging digital banking services such as mobile banking, e-wallets, and online loan platforms, rural entrepreneurs can access financial resources, manage transactions efficiently, and participate in broader economic activities. The findings reveal that digital banking reduces barriers to credit access, increases financial literacy, and promotes entrepreneurship. Furthermore, it enables rural businesses to integrate into the digital economy, fostering resilience and growth in local markets. However, challenges such as digital literacy gaps, infrastructure limitations, and trust issues must be addressed to maximize the potential of banking digitalization. This study underscores the importance of collaborative efforts among policymakers, financial institutions, and community stakeholders to ensure equitable access and sustainable development in rural areas. Keywords: Banking digitalization, rural communities, business capacity, financial inclusion, digital economy